2022
DOI: 10.1001/jamanetworkopen.2022.46064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Care Quality Metrics in 2-Sided Risk Medicare Advantage vs Fee-for-Service Medicare Programs

Abstract: ImportanceMedicare Advantage is associated with improved health outcomes, increased care efficiency, and lower out-of-pocket costs compared with fee-for-service (FFS) Medicare. When engaged in 2-sided risk arrangements, physicians are incented to offer high value for patients; however, no studies have explored the quality and efficiency outcomes in 2-sided risk Medicare Advantage models compared with FFS Medicare.ObjectiveTo compare quality and efficiency of care between physicians using a Medicare Advantage 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Studies have shown that MA-enrolled patients have improved health outcomes across multiple metrics versus traditional Medicare beneficiaries. Importantly, the largest documented benefit is a reduction in COPD or asthma hospitalizations among beneficiaries whose physicians participated in a two-sided risk MA model compared with traditional Medicare ( 19 ). In a two-sided risk model, physicians may generate financial bonuses or incur penalties based on the quality and cost of care they provide.…”
Section: Leverage Ma To Increase Pr Accessmentioning
confidence: 99%
“…Studies have shown that MA-enrolled patients have improved health outcomes across multiple metrics versus traditional Medicare beneficiaries. Importantly, the largest documented benefit is a reduction in COPD or asthma hospitalizations among beneficiaries whose physicians participated in a two-sided risk MA model compared with traditional Medicare ( 19 ). In a two-sided risk model, physicians may generate financial bonuses or incur penalties based on the quality and cost of care they provide.…”
Section: Leverage Ma To Increase Pr Accessmentioning
confidence: 99%
“…The first noteworthy finding (shown in Table I in the article by Anderson et al) is that MA enrollees are more likely to be Black, Hispanic, urban-based, Medicaid-eligible, and ‡70 years of age and to have a greater number of comorbidities but lower median income when compared with TM enrollees. These data suggest the potential for adverse selection into MA plans in this population and underscore the need for appropriate adjustment, as these demographic and clinical features are also associated with lower utilization of total joint arthroplasty (TJA) 3,12,13 . Given the stark differences in utilization of TJA between subjects in PPO and HMO plans, it would have also been useful to describe any differences in baseline demographic features between HMO and PPO beneficiaries.…”
mentioning
confidence: 94%